Intranasal administration of elastin-like polypeptide for therapeutic delivery to the central nervous system - McGowan JWD; Shao Q; Vig PJS; Bidwell III GL (Dove Medical Press, 2016)
Jeremy WD McGowan,1 Qingmei Shao,1 Parminder JS Vig,1,2 Gene L Bidwell III1,2 1Department of Neurology, 2Department of Biochemistry, University of Mississippi Medical Center, Jackson, MS, USA Abstract: Bypassing the blood–brain barrier is one of the primary considerations when designing compounds intended to function in the central nervous system (CNS). Intranasal (IN) administration of otherwise blood–brain barrier impermeable molecules can result in high CNS concentrations and low systemic accumulation, indicating that IN administration may be a useful method of delivering therapeutics to the CNS. Elastin-like polypeptide (ELP) is a large, non-immunogenic, highly manipulable biopolymer with extensive evidence supporting its use as a carrier with the ability to improve drug pharmacokinetics and drug targeting. The ability of ELP to reach the CNS via IN administration has been shown previously. Previous studies have also identified the ability of cell penetrating peptides (CPPs) to increase the uptake of molecules in some instances, including via the IN route. Here, we compared and contrasted the biodistribution of ELPs with or without addition of the CPPs Tat or SynB1 via both the IN and intravenous routes. Administration of ELP via the IN route led to significant accumulation in the brain, especially in the olfactory bulbs. When injected intravenously, <3% of the ELP signal was present outside the vascular compartment. This contrasted with IN administration, which resulted in 79% of the fluorescence signal localized outside the vascular space. The fusion of Tat or SynB1 significantly altered the biodistribution of ELP, decreasing the total CNS accumulation following IN administration. The addition of CPPs to ELP increased their retention in the nasal epithelium. These results suggest ELP may represent an effective CNS delivery vector without further modification and that the addition of a CPP significantly influences biodistribution. Keywords: central nervous system, cell penetrating peptide, elastin-like polypeptide, intranasal administration, drug delivery, blood–brain barrier